2012
DOI: 10.26719/2012.18.12.1201
|View full text |Cite
|
Sign up to set email alerts
|

Have neonatal mortality rates in the state of Qatar become static? A PEARL study analysis

Abstract: To ascertain the national neonatal mortality rate in Qatar during the first quarter of 2011 (1 January-31 March), we carried out a prospective pilot national epidemiologic study. Nationwide birth and neonatal mortality data were collected using predesigned, structured questionnaires. To analyse trends over the previous 4 years (2008-2011) we used neonatal mortality data for 2008-2010 from the database of the neonatal unit at the Women's Hospital, annual reports of Hamad Medical Corporation, and published neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Of note, there may be some disparities in healthcare between the Qatari nationals and the larger expatriate community. For instance, neonatal mortality was evaluated in the years 2008 to 2011 at Women's Hospital [42]. Neonatal mortality rates, overall in Qatar, declined very little between 2008 and the first quarter of 2011.…”
Section: Current Challenges Of the Healthcare System In Qatarmentioning
confidence: 99%
“…Of note, there may be some disparities in healthcare between the Qatari nationals and the larger expatriate community. For instance, neonatal mortality was evaluated in the years 2008 to 2011 at Women's Hospital [42]. Neonatal mortality rates, overall in Qatar, declined very little between 2008 and the first quarter of 2011.…”
Section: Current Challenges Of the Healthcare System In Qatarmentioning
confidence: 99%
“…In another of our recent article under publication,[17] we have shown that Qatar's NMR had become almost static between 2008 and 2010. The same phenomenon was observed by the developed countries during 1990's.…”
Section: Discussionmentioning
confidence: 99%
“…By 1990, virtually all NICUs had survival rates of ≥90% for infants with birth weight ≥1000 g.[56781819] From 1991 to 1997, the overall Extremely Low Birth Weight (ELBW) survival increased steadily at an approximate rate of 4% per year. However, from 1997 to 2001, there was no significant improvement in the survival of ELBW infants except those with birth weight between 500 and700 g.[19] Having achieved an NMR comparable to that in many developed countries,[391017] Qatar is now passing through the stage of achieving survival at the limits of viability. The same pattern has recently been reported from Sharjah.…”
Section: Discussionmentioning
confidence: 99%